On the timing of information release - Demski, Joel S.; Sappington, David E.M. (Information economics and policy, 1986)
We consider a simple principal-agent model in which moral hazard concerns can make it attractive to delay the release of valuable planning information. We also demonstrate that temporary manipulation of the content of the information released can be valuable.